Evaluation of patients treated by telemedicine in the beginning of the COVID-19 pandemic in São Paulo, Brazil: A non-randomized clinical trial preliminary study - Michelle Chechter; Gustavo Maximiliano Dutra da Silva; Rute Alves Pereira e Costa; Thomas Gabriel Miklos; Nilzio Antonio da Silva; Gabriel Lorber; Natacha Rivero Vasconcellos Mota; Aline Pinheiro dos Santos Cortada; Luciana de Nazare Lima da Cruz; Paulo Macio Porto de Melo; Bruno Campello de Souza; Francisco G. Emmerich; et al. (Heliyon, 2023)
We performed a pilot open-label, non-randomized controlled clinical trial in a clinic in São Paulo, Brazil in the beginning of the COVID-19 pandemic.“This medical pilot project was carried out during the pandemic of a new and unknown agent. It was necessary to find a new and safe therapeutic approach for pathogens with high potential for severity and contamination. The repositioning of safe and accessible pre-existing and approved medications and the telemedicine approach improved treated covid patients’ symptoms and reduced the risk of disease transmission. The emergency application of a new medical technology was the major limitation of the study. This innovative care model is a low-cost safe strategy, and we understand that applicability can be expanded to other regions in emergency situations.”The 187 patients of the study (mean age of 37.6 ± 15,6 years) were divided into four groups: (1) asymptomatic, (2) mild symptoms, (3) moderate symptoms and (4) severe symptoms and were followed up for five days. A drug intervention was performed in group 3 and the patients of Group 4 were oriented to seek hospital care. Of all the patients, 23.0% were asymptomatic, 29.4% reported mild symptoms, 43.9% moderate symptoms and 3.7% severe symptoms. Three patients were hospitalized and discharged after recovery. Our results indicate that the use of telemedicine with diagnosis and drug treatment is a safe and effective strategy to reduce overload of health services and the exposure of healthcare providers and the population. The patients that initiated the treatment in the early stages of the disease presented satisfactory clinical response, reducing the need of face-to-face consultations and hospitalizations. The patients who followed the protocol treatment for COVID-19 with hydroxychloroquine and azithromycin for five days presented statistically significant improvement of clinical symptoms when compared to moderate patients who opted for not following the protocol (p < 0.05) and to all no treatment patients (p < 0.001).